1999
DOI: 10.1023/a:1007022426131
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Carbohydrate-peptide esters which mimic the reactivity of sugar 6-phosphates in nonenzymatic glycations were used as model compounds for the study of the Maillard reaction in vitro. We found that intramolecular cyclization of the monosaccharide ester in which the sugar moiety (D-glucose or D-galactose) is linked, through the C-6 hydroxy group, to the C-terminal carboxy group of the endogenous opioid pentapeptide leucine-enkephalin, in methanol as the solvent, resulted in the formation of imidazolidinone diaste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…As reported earlier, [21][22][23]26 the equilibrium compositions of the Amadori compounds 1-4 show in water and DMSO solution pyranose and furanose forms, the ␤-pyranose tautomer being the most abundant. Quite surprisingly, DMSO solutions of compounds 1-4 contain at equilibrium a relatively high proportion of the acyclic hydrate form (ca.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…As reported earlier, [21][22][23]26 the equilibrium compositions of the Amadori compounds 1-4 show in water and DMSO solution pyranose and furanose forms, the ␤-pyranose tautomer being the most abundant. Quite surprisingly, DMSO solutions of compounds 1-4 contain at equilibrium a relatively high proportion of the acyclic hydrate form (ca.…”
Section: Resultssupporting
confidence: 65%
“…[21][22][23] We found that glycation of leucine-enkephalin at the Nterminal induces changes in the peptide conformation and results in total loss of opioid activity in vitro. 24 These findings are not only of theoretical interest since similar adducts with altered interactions with endogenous opioid receptors can be formed during exposure of enkephalins, or other opioid peptides, to glucose in vivo.…”
Section: Introductionmentioning
confidence: 95%
“…[26] NMR Spectroscopy: NMR experiments were carried out at a concentration of 6 m in CD 3 CN at 25°C on 400 and 600 MHz Varian Inova spectrometers equipped with 5 mm PFG triple-resonance probes, unless otherwise stated. Assignments of 1 H and 13 C resonances were carried out using standard 2D NMR techniques.…”
Section: Methodsmentioning
confidence: 99%
“…[26,27] Two isomers may be formed in the intramolecular reactions. However, the transformation of 3 into the corresponding imidazolidinone compound took place with complete stereoselectivity, resulting in the formation of (2R)-6 in which the pentitolyl residue and hydroxybenzyl group have a trans arrangement and C2 of the imidazolidinone ring has the R configuration.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the early glycation products, in our recent studies we used carbohydrate‐peptide esters in which the sugar moiety ( D ‐glucose, D ‐mannose, or D ‐galactose) is linked through its C‐6 hydroxy group to the C‐terminal carboxy group of the endogenous opioid pentapeptide leucine‐enkephalin (H‐Tyr‐Gly‐Gly‐Phe‐Leu‐OH) as model compounds for the study of the Maillard reaction in vitro 12–14. We found for the first time that, depending on the reaction conditions, in addition to Amadori rearrangement, an alternative pathway for the carbohydrate‐induced modification of peptides is possible, yielding hexose‐related imidazolidinones 13,. 14 These results point to the possibility that, depending on the physiological environment, similar carbohydrate‐related imidazolidinones may also be generated as products of the early stage of the Maillard reaction in vivo .…”
mentioning
confidence: 99%